HUBUNGAN KARAKTERISTIK DOKTER PENANGGUNG JAWAB PELAYANAN (DPJP) TERHADAP KEPATUHAN PENGISIAN RESUME MEDIS PASIEN BADAN PENYELENGGARAAN JAMINAN SOSIAL KESEHATAN (BPJS) (Studi di Instalasi Rawat Inap Rumah Sakit Islam Jemursari Surabaya) - Azizah Anisafitri (Universitas Airlangga, 2019)
A medical resume is an important document containing a summary of patient care while they are in hospital. The filling of the medical resume affects the claim process of the National Health Insurance (NHI) program. Medical resume is filled by Medical Doctor in Charge (MDiC). A preliminary study at private hospital “RSI Jemursari Surabaya” showed 86,67% incomplete BPJS claim files because there were no medical resumes. The purpose of this study was to analyze the level of medical obedience in filling medical resume and the factors that influenced based on individual characteristics. It was a descriptive quantitative study, and the measuring tools used in this study consisted of questionnaire, observation, and checklist of medical resume sheet. Variables for individual characteristics in this study included gender, age, length of employment, employment status, and specialization groups. Analysis in this study used cross tabulation. The results showed that the obedience of medical resume filling was good. MDiC that tended to be less obedient in filling medical resume had the characteristics of being a woman, aged more than 40 years old, having length of employment for more than five years, being in the group of partner-doctor, and classified as non-surgical doctor. MDiC’s obedience in filling medical resume can be improved by providing socialization of the importance of medical resume and making compliance of medical resume filling as an indicator of performance appraisal.